Pengaruh Penggunaan Web Sebagai Media Pembelajaran PKN Kelas X di SMK Muhammadiyah 1 Kuningan - Pratama, Latif; Ripai, Ipan (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine the influence of the use of the web as a learning medium for class X PKN at SMK Muhammadiyah 1 Kuningan. The method in this study uses experiments and types of quantitative research with a one group pretest posttest design. The instruments used are pretest and posttest. The data analysis techniques used were validity tests, normality tests, and paired sample t tests. This research was carried out at SMK Muhammadiyah 1 Kuningan with a sample of 18 students of class X Hospitality. The results of the study show that the learning outcomes of students in PKN learning before using web blogs as a learning medium are far from the KKM (Minimum Completeness Criteria) score with an average of 62.61. The learning outcomes of students in PKN learning after using web blogs as a learning medium have increased with an average score of 78.78. The results of the paired sample t-test Ha were accepted and Ho was rejected because of sig. (2-tailed) 0.001 < 0.05. This means that there is an influence on student learning outcomes before and after using web blogs as a learning medium